Transformational processes of situational-motor abilities of young basketball players under the influence of ten months basketball programs - Hodzic, A.; Mahmutovic, I.; Mahmutovic, E. (Sport Science - International Scientific Journal of Kinesiology, 2015)
The purpose of this study is establishing the influence of programmed training process on development of situational motor abilities in young basketball players. Transformational processes were researched on a sample of 40 subjects age 12-14 of Youth Basketball Club ¨Sloboda¨ Tuzla. Variables that were used for the assessment of situation motor abilities were: variables for the assessment of coordination of arms & legs with a ball, variable for the assessment of a ball control, variable for the assessment of movement in defense in 30 second period, variable for the assessment of movement in defense, variable for the assessment of a shoot from 5 positions, variable for the assessment of a fast shoot in 60 second period, variable for the assessment of a shoot in a ball in 30 second period, variable for the assessment of 20 m dribbling, variable for the assessment of dribbling control & variable for the assessment of agility run with a ball. On the basis of gathered and analyzed results & through factor analysis, canonic discriminative analysis & analysis of partial both quantitative & qualitative changes in a domain of situation motor abilities of young basketball players of the Youth Basketball Club ¨Sloboda¨Tuzla. Applied trainings during the period of 10 months gave both positive results and progress and improvement of basketball players` abilities.